Morphometric Feather Shells (Anadara antiquata) in Balauring and Dolulolong Waters, Lembata District - Astuti Arni; Yudiana Jasmanindar; Welem L. Turupadang (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2025)
Shellfish (Anadara antiquata) is a type of marine biota from the bivalve class. This species is a vital source of income for coastal communities. This study aims to compare the morphometry and population density. The method used is line transect and quadrant transect. The size of the quadrant/plot is 2x2 m², and the distance between 1 quadrant and another quadrant is 2 m. The data analysis used is multiple linear regression and the t-test. The results showed that the morphometric length of the shells in the waters of Balauring Village = 22.7 mm, in the seas of Dolulolong = 25.9 mm, the width in the waters of Balauring Village = 15.6 mm, in the waters of Dolulolong Village = 18.4 mm, the height in the seas of Balauring Village = 12.3 mm, in Dolulolong waters = 17.1 mm, while the weight of clams in Balauring Village waters = 4.3 grams and in Dolulolong Village waters = 4.8 grams, and the value of the population density of shellfish for point I = 0.55 ind/m², point II = 0.94 ind/m², and point III = 1.01 ind/m². The morphometrics in Balauring waters are greater than in Dolulolong waters. The population density in Balauring and Dolulolong waters did not experience a significant difference.